2020
DOI: 10.1109/access.2020.3016780
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Detection Through Transfer Learning Using Multimodal Imaging Data

Abstract: Detecting COVID-19 early may help in devising an appropriate treatment plan and disease containment decisions. In this study, we demonstrate how transfer learning from deep learning models can be used to perform COVID-19 detection using images from three most commonly used medical imaging modes X-Ray, Ultrasound, and CT scan. The aim is to provide over-stressed medical professionals a second pair of eyes through intelligent deep learning image classification models. We identify a suitable Convolutional Neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
300
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(308 citation statements)
references
References 88 publications
4
300
0
4
Order By: Relevance
“…The final accuracy reported by these researchers for separating the two classes is reported to be about 96%. Horri et al [30] used 3 types of medical imaging (X-ray, Ultrasound, and CT) to automatically detect the two classes of COVID-19 and healthy. In their research, they used an optimized deep VGG transfer learning network.…”
Section: Introductionmentioning
confidence: 99%
“…The final accuracy reported by these researchers for separating the two classes is reported to be about 96%. Horri et al [30] used 3 types of medical imaging (X-ray, Ultrasound, and CT) to automatically detect the two classes of COVID-19 and healthy. In their research, they used an optimized deep VGG transfer learning network.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent studies have shown that machine/deep learning techniques are technologies used in all branches of health sciences as elements of clinical decision support and as generators of new clinical knowledge [ 19 , 20 , 21 ]. In this regard, multiple research projects have been published using machine/deep learning techniques for the early detection of the COVID-19 virus [ 22 , 23 , 24 , 25 ], models applied to patients admitted to ICUs, which have been the clinical units most affected by the virus [ 26 , 27 , 28 ], and machine/deep learning applied in “omic” technologies to predict complications of COVID-19 [ 29 , 30 ]. The number of published papers about COVID-19 is continuously growing [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first four blocks of the VGG16 architecture pre-trained on ImageNet weights are used for this purpose [13,17]. Since the Image net set is non-overlapping to the problem, the last 8 layers, i.e., the third and fourth convolution blocks are fine-tuned on the augmented CT scan training data [40]. While training these, it is desired that the fourth block adapts more to the data compared to the third block.…”
Section: Transfer Learningmentioning
confidence: 99%